Prognostic implications of adherence to oral anticoagulants among patients with atrial fibrillation: Insights from MISOAC-AF trial. Issue 4 (April 2023) - Patsiou, Vasiliki; Samaras, Athanasios; Kartas, Anastasios; Moysidis, Dimitrios V.; Papazoglou, Andreas S.; Bekiaridou, Alexandra; Baroutidou, Amalia; Ziakas, Antonios; Tzikas, Apostolos; Giannakoulas, George
Abstract: Objectives: To explore the implications of adherence to oral anticoagulants (OACs) on all-cause mortality and cardiovascular outcomes in patients with atrial fibrillation (AF). Methods: This post-hoc analysis of the MISOAC-AF trial included recently hospitalized patients with AF. Adherence to OACs was assessed by the proportion of days covered (PDC). Good adherence was defined as PDC >80 %. Cox regression models were used to associate PDC with clinical outcomes of all-cause death, cardiovascular death (CVD), stroke, and bleeding. A sub-analysis was performed among adherent patients to compare outcomes between vitamin K antagonists (VKAs) and direct oral anticoagulants (DOACs). Results: During a median 31-month follow-up, 778 cardiac patients with comorbid AF who had been prescribed OACs upon hospital discharge were studied. The mean PDC was 0.78; 66 % of patients had good adherence (>80 %) which was associated with lower risk of all-cause death [adjusted hazard ratio (aHR): 0.64; 95 % confidence interval (CI): 0.46 to 0.84, p  < 0.001] and CVD (aHR: 0.70; 95 % CI: 0.50 to 0.97, p  = 0.03). The risk of stroke and major or non-major bleeding did not differ by adherence status. Among adherent patients to OACs, VKA use was associated with higher rates of all-cause death ( p  < 0.001), CVD ( p  < 0.001), and stroke ( p  = 0.01); no differences were found regarding major or non-major bleeding risk. Conclusions: In recently hospitalized patients with AF, good adherence to OACs was associated with a reduced risk of all-cause death and CVD. The rates of stroke or bleeding events were not significantly different. VKAs were associated with more adverse events compared to DOACs. Graphical abstract: Unlabelled Image Highlights: 1/3 of patients with atrial fibrillation had poor adherence to oral anticoagulants. Good adherence to oral anticoagulants was related to less adverse events. Acenocoumarol was associated with more adverse events than direct oral anticoagulants.